Topological Flatband Loop States in Fractal-Like Photonic Lattices - Song, Limin; Xie, Yuqing; Xia, Shiqi; Tang, Liqin; Song, Daohong; Rhim, Jun Won; Chen, Zhigang (Laser and Photonics Reviews, 2023)
Noncontractible loop states (NLSs) are a recently realized topological entity in flatband lattices, arising typically from the band touching at a point where a flat band intersects one or more dispersive bands. There exists also band touching across a plane, where one flat band overlaps another all over the Brillouin zone without crossing a dispersive band. Such isolated plane-touching flat bands remain largely unexplored. For example, what are the topological features associated with such flatband degeneracy? Here, nontrivial NLSs and robust boundary modes in a system with such degeneracy are demonstrated. Based on a tailored photonic lattice constructed from the well-known fractal Sierpinski gasket, the wavefunction singularities and the conditions for the existence of the NLSs are theoretically analyzed. It is shown that the NLSs can exist in both singular and nonsingular flat bands, as a direct reflection of the real-space topology. Experimentally, directly such flatband NLSs in a laser-written Corbino-shaped fractal-like lattice are observed. This work not only leads to a deep understanding of the mechanism behind the nontrivial flatband states, but also opens up new avenues to explore fundamental phenomena arising from the interplay of flatband degeneracy, fractal structures, and band topology.
Keywords: A-plane; Dispersive band; Flat band; Fractal-like; Fractal-like lattice; Nonsingular; Nontrivial loop state; Singular and nonsingular flat band; Singularity; Topological entity; fractal-like lattices; nontrivial loop states; singular and nonsingular flat bands; singularity; topology